Numerical studies on the seismic responses of bridge structures with precast segmental columns. (15th November 2017) - Zhao, Lufeng; Bi, Kaiming; Hao, Hong; Li, Xiaozhen
Highlights: Seismic responses of bridge structures with segmental columns are numerically investigated. Seismic responses of bridge structures supported by segmental columns and monolithic columns are compared. The influences of pounding, frequency ratio and gap size are systematically investigated. Abstract: Recently, extensive experimental and numerical studies have been carried out to understand the seismic behaviors of segmental columns. Very limited studies, however, focused on the seismic performances of a whole bridge system with precast segmental columns. This paper carries out numerical studies on the seismic responses of bridge structures with precast segmental columns. For comparison, the seismic responses of the bridge with conventional monolithic columns are also calculated. The two-dimensional (2 D) finite element (FE) models of these two bridge types are developed by using the FE code OpenSEES. The segmental column and monolithic column are simulated by the simplified lumped-mass model and fiber-based model respectively and validated by the previous experimental studies. The calibrated column models are then incorporated into the whole bridge structures to calculate the structural responses. The influences of pounding, frequency ratio and gap size on the structural responses are investigated and discussed. Numerical results show that the bridges supported by the segmental columns or monolithic columns have very different seismic responses.